(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The study looked at how consumer behaviour affected the value of residential real estate in Nigeria’s Edo State capital of Benin. Self-completed questionnaires were employed in the study to gather pertinent information. Professionals working for surveying and valuation companies in the city of Benin filled out 59 successfully completed questionnaires. To support the hypothesis, the data were analysed using the chi-square test method and presented as frequency and percentage tables. The study discovered that although there have been cases in Benin of customers trying to sway assessment reports, these occurrences are negligible since appraisers don’t let such clients’ influence have an impact on their ratings. To avoid effects such as overvaluation, undervaluation, misvaluation, professional misconduct, and legal and litigation cases on the valuation reports, appraisers are urged to continue resisting client influence in order to produce valuation reports that serve as strong market evidence for additional reference.